Controlling Image Color Programming and Thinking Outside the Box to Achieve Additional Results for the Image - Abood, Khaleel I.; Zaeen, Ahmad Asaad; Jawad, Laith Aziz (Iraqi Journal of Science, 2026)
This research is primarily an educational applied study, where a step-by-step MATLAB program has been written (unlike other ready-made programs). This allows researchers to modify, add, or remove any steps that suit their work in the program and what they find most appropriate for their tasks. The program is based on the spectral signature of the colors present in the map; it selects an area composed of 30×30 pixels or 20×20 pixels in a desert region, for example. The program recognizes its basic colors to identify all similar areas throughout the map and other regions, whether they are fertile areas, semi-desert regions, or water bodies. This research is a guide on applying for a program in MATLAB step by step to reach wide applications in image processing. It is not a compiled program, but it was written by the researchers manually so that users have wide options for entering equations as desired and without restrictions. Users may choose the same equations in the program by changing some constants to change results. Each map may be taken indoors to a specific area or even to the entire Earth by satellites in a unique pattern chosen by users. All that has to be done is input values defining the regions (desert regions, semi-desert regions, fertile agricultural regions, etc.), as has been done in this research. Through image processing, different regions were identified and accurately determined, and the areas of those regions were calculated using a map of Iraq using the Google Earth tool 530×530 pixels (68 KB). The color gradation of the three RGB colors in each region was taken, and they were determined by the minimum and maximum values for each color; the colors will be automatically chosen. These conditions were generalized to the entire map and subsequently identified automatically by the program. Good values were obtained from this method, as seen in the research where the desert lands represented 29.85% of Iraq's area, semi-deserts were almost 7.6 %,  the lands which can be reclaimed were nearly 8.7 %, wetlands with deep groundwater were roughly 13.9%, wetlands with water close to the surface were almost 15.7 %. Finally, fertile agricultural lands represented roughly 14.6% of Iraq’s areas.